Review of the tribe Helconini Foerster s.s. from China, with the description of 18 new species - Yan, Cheng-Jin; Achterberg, Cornelis Van; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2017)
The Chinese species of the tribe Helconini Foerster, 1863 s.s. (Hymenoptera, Braconidae, Helconinae) are reviewed. The tribe Helconini Foerster and its genera are redefined and a key to the genera of the tribe is given. Gymnoscelus rufithorax Turner, 1918, is provisionally transferred to the genus Parahelcon Kokujev, 1901 (comb. nov.). The Chinese species belonging to the genera Acarohelcon gen. nov. (type species: Acarohelcon varicolor sp. nov.), Helcon Nees, 1812, Helconidea Viereck, 1914, and Wroughtonia Cameron, 1899 (including Spasskia Belokobylskij, 1989, syn. nov.), are keyed, described and illustrated. Eighteen new species are described from China: Acarohelcon. varicolor sp. nov., Helcon sulcatus sp. nov., Wroughtonia acuta sp. nov., W. albobasalis sp. nov., W. areolata sp. nov., W. bifurcata sp. nov., W. breviantennata sp. nov., W. brachygena sp. nov., W. chui sp. nov., W. eurygenys sp. nov., W. hei sp. nov., W. jiangliae sp. nov., W. nigrifemoralis sp. nov., W. obtusa sp. nov., W. rugosa sp. nov., W. varifemora sp. nov., W. yaanensis sp. nov., and W. zhejiangensis sp. nov., Four species are reported for the first time from China: Helconidea dentipes Tobias, 1967, Wroughtonia planidorsum Watanabe, 1952, W. sibirica (Tobias, 1967) and W. unicornis (Turner, 1918). Helcon albus Chou et Hsu, 1998, H. claviventris Wesmael, 1835, H. orientalis Shestakov, 1940, Helconidea nigra Tobias, 1967, H. sibirica Tobias, 1967, Spasskia anastasiae Belokobylskij, 1998, S. brevicarinata Yan et Chen, 2014, S. indica Singh, Belokobylskij et Chauhan, 2005, and S. sigalphoides Belokobylskij, 1989, are transferred to the genus Wroughtonia (comb. nov.) and Helconidea duplidentipes Shenefelt, 1970, is replaced by H. dentipes Tobias, 1967 (reinstated). Duportia cincticornis Kieffer, 1921, is synonymized with Wroughtonia unicornis (Turner, 1918) syn. nov.